Optimalisasi Pendayagunaan Mediasi Sebagai Alternatif Penyelesaian Sengketa Merek - Aryani, Fajar Dian; Pratama, Erwin Aditya; Indriasari, Evy (Diktum: Jurnal Ilmu Hukum, 2021)
Various forms of administrative legislation and/or economic administration laws that "involve" criminal law in Indonesia are quite numerous. One example is Law No. 20 of 2016 on Brands And Geographic Indications. The problem of criminal law in the field of administrative law as well as economic law, especially in the enforcement and protection of intellectual property rights has not shown action in line with the spirit of the establishment of the law. One form of violation of the law that is currently developing in Indonesia is the duplication of copyright. But so far efforts to provide legal protection for copyright holders appear to be inadequate. Even in the process of implementing law enforcement, it is not uncommon for copyright infringement cases to be down the road. Seeing problems in the enforcement of economic criminal law, especially in the field of intellectual property rights, gives rise to alternative discourse on resolving criminal disputes in the field of intellectual property rights, especially against brand rights violations. Whether the criminal activity in the field of the brand can be solved outside the Court That in Penal Mediation there are parties involved in the process of handling it, namely Victims, Perpetrators, Community and Community Leaders (village chiefs/ chiefs) or other parties (Law Enforcement) as neutral persons to be used as Mediators to help the parties in dispute to reach a settlement in the form of voluntary agreement on some or all of the disputed issues. The mediator's job is to make the parties forget the legal framework and encourage them to engage in the communication process. As mediators in criminal cases can be raised by the investigators themselves, therefore the Investigator in the implementation of Penal Mediation must be neutral, or impartial to either party to the dispute.